Establishing relevant and high quality domestic MRV systems to support effective climate action - Letete, Thapelo Clifford Mohale (Department of Mechanical Engineering, 2023)
The adoption of the United Nations Framework Convention on Climate Change (UNFCCC or Convention) at the 1992 Rio Earth Summit marked a decisive global turning point in the fight against anthropogenic climate change. The ultimate objective of the Convention is to stabilize greenhouse gas concentrations at a level that would prevent dangerous anthropogenic interference with the climate system within a time frame that allows ecosystems to adapt naturally to climate change. Transparency, through ‘Measurement, Reporting and Verification' (MRV), is one of the key elements of the Convention, required to build mutual trust and confidence and to promote effective implementation. The wording of the Framework Convention itself contains various provisions for MRV, with the information requirements and the frequency for MRV differentiated substantially between developed and developing country Parties. Termed 'the UNFCCC MRV Framework', these MRV requirements together with the related MRV activities within the Convention have been evolving, almost continuously over the years, with the adoption of every major decision by the COP and as calls for more transparency by Parties increase. The Paris Agreement, which is the latest agreement under the Convention, contains the most demanding MRV requirements to date. To enable themselves to adequately respond to these MRV requirements, Parties to the UNFCCC have been establishing domestic MRV systems. However, the constant evolution of the UNFCCC MRV framework as well as the countries' domestic policies, strategies and laws which keep coming with their own MRV requirements have made ensuring full relevance of these systems to all their reporting requirements as well as maintaining high quality of their outputs a challenge, thereby jeopardizing the ability of those MRV systems to effectively support climate action. This thesis set out to investigate the factors that affect the success and failure of establishing domestic MRV systems that are fully relevant to the countries' information requirements and of high quality, and to determine a framework which countries can use to establish such systems. The thesis investigated the hypothesis that ‘results-based planning through logical modelling ensures maximum relevance of domestic MRV systems and improves their quality.' In terms of relevance of domestic MRV systems, it was found that relevance can be fully achieved at the planning phase by ensuring that the system's objectives and envisaged outcomes are fully aligned with the country's MRV needs. Furthermore, it was concluded that results-based planning through logical modelling, if undertaken properly, comprehensively, and by an adequately skilled and experienced team, and ideally coupled with monitoring and evaluation, can lead to maximum relevance of the domestic MRV systems. In terms of quality, it was found that transparency, accuracy, completeness, comparability, consistency and timeliness (TACCCT) adequately capture the quality of domestic MRV systems, and that availability of resources, frequent reporting, third party expert reviews assist in the improvement of the quality for domestic MRV systems. Furthermore, it was determined that only following the steps of results-based planning on their own does not improve the quality of domestic MRV systems, rather it is inclusion of the second part of the planning phase, focusing on monitoring and evaluation, that leads to improved quality of domestic MRV systems. This combination of results-based planning with monitoring and evaluation is also known as results-based management. The main contribution of this thesis is then the development of a framework that countries can use to establish relevant and high quality domestic MRV systems to support effective climate action.